Collective memory and social identity - Kuzmanić, Marja (Psihološka obzorja (Ljubljana), 2008)
Through narration of memories of events related to the disintegration of Yugoslavia, this study takes a social psychological approach and explores the generational and ethnic group differences in collective memories, social representations and social identities of peoples living in Slovenia. It represents an initial step at mapping out the differing collective memories, representations and identities of Slovenians and other former Yugoslav peoples now resident in Slovenia in relation to some of the major recent historical and political events (Tito's death, the wars in Slovenia, Bosnia and Croatia, the beginning of the war(s), and the attainment of independence of Slovenia). Eighteen semi-structured interviews with members of three ethnic communities (Bosniac and Serb minority and Slovenian majority) were conducted and are qualitatively analysed. The findings are discussed in two sections. The first illustrates the contested interpretations of the break up of the federation, whereas the second section discusses the complex changes inidentification that occurred during the transition in the Slovenian context. Above all, the material reveals that contested narratives of the breakup of Yugoslavia (the narratives of 'transition', 'disintegration' and 'war') are present.
Keywords: kolektivni spomin; socialna identiteta; socialna psihologija; social psychology; pripovedovanje; razpad Jugoslavije; Yugoslav Wars; Slovenia; Slovenija